Evaluation of Law Enforcement Policy on Criminal Acts in Cooperatives - M. Irwan Susanto; Abdullah Sulaiman (Greenation International Journal of Law and Social Sciences, 2025)
This study aims to evaluate law enforcement policies concerning criminal acts within cooperatives in Indonesia. As membership-based economic institutions, cooperatives play a strategic role in enhancing community welfare; however, they remain vulnerable to criminal acts, particularly those related to abuse of authority and embezzlement of members’ funds. This research employs a mixed methods approach, combining a juridical-normative analysis of statutory regulations and legal doctrines with an empirical approach through case studies, interviews, and surveys involving cooperative managers, supervisors, members, and relevant law enforcement officers. The findings reveal that the existing law enforcement policies are not yet fully effective in providing legal protection and certainty for cooperative members. The ineffectiveness is mainly attributed to regulatory limitations, weak inter-agency coordination among law enforcement bodies, and the insufficient participation of members in supervisory mechanisms. Accordingly, reformulating a more comprehensive law enforcement policy, strengthening supervisory institutions, and implementing governance principles grounded in transparency and accountability are deemed essential to prevent and address criminal acts within cooperatives more effectively.